The road to El Dorado [videorecording (DVD)] - Bergeron, Bibo; Paul, Don C. (Universal Pictures Home Entertainment, 2018)
Two adventurers accidentally end up on a ship to the New World and once there, they unintentionally discover El Dorado, the city of gold.